BEACHROCKS CEMENT CHARACTERISTICS AND CONDITIONS OF FORMATION. CASE STUDY PLATANIAS BEACH, CHANIA, GREECE - Petropoulos, A.; Baziotis, I.; Anagnostou, Ch.; Evelpidou, N. (Bulletin of the Geological Society of Greece, 2016)
Beachrocks represents a coastal deposition in the intertidal area, and studying their properties may lead to create a model which identifies the conditions of their formation (paleo-environment). This paper focuses most intently on the cement material which is able to recover the paleo-environment conditions during diagenesis of such coastal sediment. We used optical microscopy, secondary electron microscopy and Raman Spectroscopy to characterize the cement texture, mineralogy and chemistry in the beachrocks. The existence of pure calcite primarily controlled by the meteorite water, while Mg-calcite appears between the lowermeteoric and the upper marine phreatic zone. Finally, the presence of aragonite associated with the marine phreatic to lower marine vadose environment.